The Blue Compendium 2023
DOI: 10.1007/978-3-031-16277-0_17
|View full text |Cite
|
Sign up to set email alerts
|

The Ocean as a Solution to Climate Change: Five Opportunities for Action

Abstract: The ocean is a dominant feature of our planet, covering 70% of its surface and driving its climate and biosphere. The ocean sustains life on earth and yet is in peril from climate change.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 182 publications
2
8
0
Order By: Relevance
“…The findings of the authors are confirmed [1,4], highlighting the importance of the port location to maximize the utilization of offshore wind potential, emphasizing that welllocated ports facilitate logistics operations and reduce costs, corroborating Hypothesis 1, that location is a crucial factor for the performance and sustainability of ports associated with floating wind turbines. The statements discussing the need for specialized port infrastructures equipped with quays to support high-capacity cranes and support for offshore vessels to efficiently support the operations of floating wind turbines [19,32] were validated, confirming Hypothesis 2, that infrastructure is fundamental for the performance and sustainability.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…The findings of the authors are confirmed [1,4], highlighting the importance of the port location to maximize the utilization of offshore wind potential, emphasizing that welllocated ports facilitate logistics operations and reduce costs, corroborating Hypothesis 1, that location is a crucial factor for the performance and sustainability of ports associated with floating wind turbines. The statements discussing the need for specialized port infrastructures equipped with quays to support high-capacity cranes and support for offshore vessels to efficiently support the operations of floating wind turbines [19,32] were validated, confirming Hypothesis 2, that infrastructure is fundamental for the performance and sustainability.…”
Section: Discussionsupporting
confidence: 52%
“…The offshore energy sector has witnessed remarkable growth and attention in recent years, primarily driven by global concerns over energy and issues related to climate change [1]. In this context, various nations have formulated policies to explore renewable energy sources and meet the growing energy demand [2,3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the United Nations Framework Convention on Climate Change (UNFCCC) is based on a 100 year time horizon, whereas most current national climate policies, formalized through NDCs, are on shorter timescales. Many estimates of the potential contribution of nature-based solutions to climate mitigation (Hoegh-Guldberg et al, 2019) are also based on their role in helping to close the emissions gap by 2030 or 2050. For such time periods, the sustained-flux GWP (SGWP) and sustained-flux global cooling potential (SGCP) for CH 4 emissions is around twice as high as end of century values; however, there is little difference for N 2 O (Neubauer & Megonigal, 2015).…”
mentioning
confidence: 99%